Interparietal Bone Variations in Accordance with their Ossification Centres in Human Skulls - Khan,Aaijaz Ahmed (Sociedad Chilena de Anatomía, 2013)
The upper interparietal segment of the squamous part of the occipital bone develops in membrane and the lower supraoccipital part develops in cartilage. According to the available literature, the interparietal segment is ossified from 2 to 3 pairs of ossification centres and each of these centres has 2 nuclei. Interparietal bone is formed due to failure of fusion of these centres and/or their nuclei with each other. Many variations of interparietal bone have been reported by many investigators. In the present study, out of 25 human skulls studied, six skulls had some interesting variations of interparietal bones. Four interparietal bones were found in one skull, 2 interparietal bones were observed in another skull and the remaining four skulls had a single interparietal (Os inca) bone at the lambda. In addition to interparietal bones, some sutural bones were also observed in three skulls. These variations were in accordance with the ossification centres of the membranous part of the occipital bone. By their location and shape it was concluded that they were formed due to failure of fusion of nuclei of the third pair centres of ossification with each other, with opposite fellow and with the second pair centers. It was further concluded that these cases of interparietal bones were different from what had been reported earlier by other researchers and this prompted the present report that may be found useful for anatomists, anthropologists, radiologists and neurosurgeons.